Unusual Presentation of Cutaneous Spindle Cell Squamous Cell Carcinoma: A Case Report - Erika Wernheden; Hannah Trøstrup; Anette Pedersen Pilt (Karger Publishers, 2020)
Cutaneous spindle cell squamous cell carcinoma (SpSCC) is a rare and often aggressive subtype of squamous cell carcinoma (SCC), which usually appears in sun-exposed areas, in areas that have received prior ionizing radiation, or in immunosuppressed individuals. SpSCCs are histologically characterized by keratinocytes infiltrating the dermis as single cells with elongated nuclei rather than as cohesive nests or islands and, in contrast to conventional SCC, are lacking features of keratinization. Immunohistochemical studies are useful to distinguish SpSCC from other spindle cell neoplasms, such as spindle cell/desmoplastic melanoma, cutaneous leiomyosarcoma, and atypical fibroxanthoma. We present a rare case of a patient with SpSCC in the gluteal region with regional lymph node metastasis. The patient was treated with wide excision of the tumor, inguinal lymph node dissection, and adjuvant radiotherapy. Cutaneous SpSCC is clinically similar to conventional SCC but can demonstrate more aggressive behavior. This case is rare since it was localized in the gluteal region of an otherwise healthy man.